UKRAINIAN ENTREPRENEURSHIP IN POLAND: CHALLENGES AND OPPORTUNITIES - Valentyna Smachylo; Olha Rudachenko; Oleh Kulinich; Dmytro Simonov (Academy Review)
The article is devoted to solving the problem of developing Ukrainian business projects in the Polish market. The article analyzes scientific methods that incorporate both qualitative and quantitative principles. These methods include quantitative methodology (positivist), based on quantitative research; qualitative methodology (interpretive), focused on qualitative research; and mixed methodology, which combines both approaches. It is demonstrated that, among the examined methods, interviews are the most commonly used data collection format by the authors. The selection of experts for the interviews was based on an analysis of the consulting services market, specifically firms that assist Ukrainian entrepreneurs in Poland. Through the experts’ insights, typical characteristics of Ukrainian entrepreneurs entering the Polish market were identified: 1. Self-confidence; 2. Non-perception/ misunderstanding of mental and cultural features on the Polish market; 3. “Allergy” to paying taxes; 4. Unwillingness to pay for consultations; 5. Unpreparedness for business analysis; 6. Unpreparedness for bureaucratization of processes; 7. Lack of a strategic vision of development; 8. Speed of doing business; 9. Orientation not on the client’s needs, but on one’s own experience or product; 10. The desire to earn a lot at once; 11. Resistance to current rules. Attempts to implement the rules of the game as in Ukraine. Also, the stages of launching new business projects in the Polish market were determined. The first stage – preparatory - often ignored by entrepreneurs and includes studying the market, understanding relevant legislation, and conducting business analytics. The second stage – entering the market – involves formalizing the business idea, business processes, and business model. The third stage – adaptation – can last anywhere from less than a year to up to five years, depending on factors such as the team’s activity level, the business field, enterprise size, and the entrepreneur’s previous experience. During this stage, the business model is reformatted, and the company aims to reach the break-even point. The fourth stage – refining – focuses on business processes and managing the business itself, with an emphasis on meeting and achieving established performance indicators. At this point, Ukrainian businesses do not differ significantly from their Polish counterparts. The final key question addressed during the interviews was identifying the problems and needs that Ukrainian business projects face when entering the Polish market. As a result of the expert interview, a problem area was formed for Ukrainian business projects entering the Polish market: • lack of business analytics for successfully starting and running a business; • misunderstanding of internal market processes of the Polish market; • problems with financing; • lack of understanding of the legislation of Polish and European standards in general, peculiarities of taxation and accounting; • low efficiency and quality of conducting business processes; • mistrust of Ukrainian brands, the need to build a brand on the Polish market from “0”; • recruitment and work with personnel; • language problems. The recommendations include: conducting a thorough study of the local business climate, adapting business strategies to align with local market realities and actively seeking partnerships and support within the local business community.